Usage of Vegetal Wastes for Energy Production - I. I. Karpunin; V. V. Kuzmich; T. F. Balabanova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An analysis on usage of vegetal wastes for energy production is presented in the paper.The paper reveals that logging debris and linen chaffs are considered as a prospective raw material for energy production in theRepublicofBelarus.